Development and lyophilization of itraconazole loaded poly(butylcyanoacrylate) nanospheres as a drug delivery system - Ćurić, Anamarija; Keller, Benjamin-Luca; Reul, Regina; Möschwitzer, Jan; Fricker, Gert (European journal of pharmaceutical sciences, 2015)
Itraconazole is a poorly soluble drug which is used in the treatment of systemic fungal infections. However, there is little reported literature about itraconazole loaded delivery systems used for targeted delivery. Therefore, poly(butyl cyanoacrylate) nanospheres (PBCA-NSP) have been developed as a potential delivery system for transport of itraconazole. One possible application of itraconazole loaded PBCA-NSP could be to treat cryptococcal meningitis. An oil-in-water (o/w) emulsion solvent evaporation was performed for formulation generation. Manufacturing optimization was achieved using design of experiments (DoE) methodology. The average size of PBCA-NSPs varied between 60 and 80nm. Encapsulation efficiency (EE (%)), absolute drug loading (AL (%)) and release rate of itraconazole from PBCA-NSP in vitro were measured by reversed phase high-performance liquid chromatography (RP-HPLC). EE of 87% could be achieved when the AL of 17.6% was intended. Lyophilization of itraconazole loaded PBCA-NSP was needed to increase the stability of formulations, which was achieved by evaluating different sugar cryoprotectants. In this study, PBCA-NSPs were successfully generated as a delivery system for itraconazole providing a promising approach to improve the therapy of fungal infections of specific organs such as the brain infection cryptococcal meningitis.
Gesehen am 15.12.2020